Conflict of Norms on the Implementation of Personal Data Protection in Insurance Companies in Indonesia - Lukman Ilman Nurhakim; Neni Sri Imaniyati; Sri Ratna Suminar (Global Writing Academica Researching & Publishing, 2026)
This study examines the harmonization of personal data protection regulations within Indonesia’s insurance sector following the enactment of Law Number 27 of 2022 concerning Personal Data Protection (PDP Law). Since its promulgation on 17 October 2022, the PDP Law has established a comprehensive normative framework governing the processing and protection of personal data. Its alignment with sectoral regulations becomes imperative, particularly in light of Law Number 4 of 2023 concerning the Development and Strengthening of the Financial Sector (PPSK Law). Article 3 paragraph (2) letter (i) of the PPSK Law explicitly affirms the objective of strengthening the protection of customers’ personal data in the financial services sector, while Article 240 paragraph (1) requires financial sector business actors, including insurance companies, to comply with prevailing personal data protection laws and regulations as well as supervisory provisions issued by the Financial Services Authority. However, in practice, the PDP Law currently fulfills primarily the element of legal substance within the legal system. The structural and legal culture components remain incomplete, as the Law mandates the issuance of ten Government Regulations and one Presidential Regulation to operationalize its provisions. The absence of these implementing instruments creates normative fragmentation and limits effective enforcement within the insurance industry. Consequently, the PDP Law predominantly reflects a preventive model of legal protection, as conceptualized by Hadjon, emphasizing anticipatory safeguards and compliance mechanisms rather than repressive enforcement. This condition highlights the urgency of regulatory harmonization and institutional strengthening to ensure coherent and effective personal data protection governance in Indonesia’s insurance sector.